Social Distancing Detection By Drone Exploration : A novel thermal images analysis model (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Facing the criticality of the COVID 19 pandemic, we propose an artificial intelligence system with a modern approach detecting people and their social distancing in crowded places using thermal images obtained from the DJI Mavic 2 Enterprise Dual drone. We implement an algorithm that analyzes two types of images: color and thermal, to measure the distance between people. We used the Fast R-CNN neural network; the images with videos were extracted from the DJI Pilot application. The objective is to identify the distance between people. The results obtained show that the proposed algorithm is suitable for monitoring the city.